Alcohol and tobacco content in UK video games and their association with alcohol and tobacco use among young people - Cranwell, J.C.; Whitamore, Kathy; Britton, John; Leonardi-Bee, Jo (Mary Ann Liebert, 2016)
Aims: To determine the extent to which video games include alcohol and tobacco content and assess the association between playing them and alcohol and smoking behaviours in adolescent players.